MULTIMEDIA INTERAKTIF BERBASIS LECTORA INSPIRE PADA SUBTEMA SUMBER ENERGI SISWA KELAS IV SEKOLAH DASAR - Angga Andhi Wibowo (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2022)
The purpose of this research is to produce and develop a product maximally in order to increase its usefulness by utilizing the facilities and infrastructure in Muhammadiyah Karangploso elementary school. The research to be carried out is in the form of thematic learning media products using Lectora Inspire media. Data collection techniques used expert validation assessment sheets (media experts, material experts and learning experts) and student response assessment questionnaire sheets. The data analysis used is quantitative and qualitative descriptive analysis by analyzing quantitative data that has been obtained from expert validation sheets and student response assessment sheets to learning media which were originally a score, then converted into qualitative data (interval data) on a scale of five. The results of this study indicate that the media using Lectora Inspire multimedia is suitable for use in learning. Interactive multimedia based on Lectora Inspire on the sub-theme of energy sources used in class four elementary schools to assist teachers in providing understanding to students on energy sources with interactive multimedia based on Lectora Inspire is very supportive when used for thematic learning on the sub-theme of energy sources for fourth grade elementary school students.